Engaging with startups: MNC perspectives. Issue 4 (December 2019) - Prashantham, Shameen; Kumar, K.
Abstract: Through a conceptual note and round table discussion, this article builds upon Buckley and Prashantham's (2016) "division of entrepreneurial labour" notion to consider more closely the perspective of multinational corporations (MNCs) in relation to partnering with startups. First, the capability dimension suggests that there is potential for value creation resulting from complementarity between the strengths of corporations and startups. Second, the connectivity dimension is concerned with how this potential is realised; the rise of corporations' programmatic initiatives and third-party specialists are highlighted. Third, the contextuality dimension highlights spatial differences, noting MNCs' unique opportunities and challenges vis-à-vis startup partnering in emerging markets.